THE BUDDY PROGRAM SUPPORT AND CULTURAL INTRODUCTION FOR STUDENTS FROM OUTSIDE BALI - Veranata .; Ni Luh Christine P. S. Suyasa; Putu Chrisma Dewi (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTThis research aims to determine whether there are preliminary interests among UniversitasDhyana Pura students from outside of Bali in a Buddy Program, the student from outside Baliexpectations for this program and what kind of assistance and activities that expected as amigrant student to reduce the possibility of cultural shock and help the incoming students toadapt in new environments and culture. This research was taken based on the results of a surveyby 34 respondents. This research method is a quantitative description which uses a groupingquestionnaire into several categories. This study found that most of the students from outsideBali agreed with the holding of the buddy program and wanted to be introduced to Balineseculture and simple Balinese Language.Keywords: Buddy Program, culture shock, studying abroad